A support programme for caregivers of cancer patients in the Palestinian context - Hayek, Mohammed F. A. (My University, 2020)
Background: Caring for a cancer patient is not easy and caregivers receive little preparation, information, and support to carry out their caregiving role. Caregivers experience physical, psychosocial/spirituals, emotional, financial distress, which increase their risk for burden, poor quality of life (QoL), and burnout. Aim: The study aimed to develop and pilot test a support programme for caregivers of cancer patients in Palestine. Methods: The study was underpinned by Lazarus and Folkman’s transactional model of stress and coping. A sequential multi-method study design which employed two scoping reviews, and an intervention design with pre-test post-test approach was used. Therefore, the study had four Phases. Phase One was a scoping review, to synthesise the evidence regarding the support needs of caregivers of cancer patients, Phase Two was the second scoping review in order to exhaust the viability of published support programmes for caregivers of patients diagnosed with cancer, Phase Three was a developed/adapted and validated a support programme for caregivers of cancer patients and Phase Four was pilot tested of the support programme. The primary outcome was caregiver QoL and secondary outcomes caregiver burden, patient pain, symptom burden and QoL. Sampling was convenience and fifty care givers (n=50) and (n=50) patients were recruited. The Caregiver QoL Index-Cancer (CQOLC) and Zarit Burden Interview (ZBI) measured caregiver outcomes and The Brief Pain Inventory (BPI), EORTC QLQ and Memorial Symptom Assessment Scale (MSAS) measured patient pain, QoL and symptom burden. Results: The first scoping review revealed that the caregivers had numerous unmet needs which were grouped in seven themes namely: information and emotional needs, cancer care services and physical, social, psychological/spiritual and financial support needs. Different caregivers support programmes were investigated from included studies in the second scoping review, which are varied in the scope of interest. All the studies were conducted in developed countries. A shared theme in most of the works that offered viii programmes was easy to understand and applicable to the participants, to facilitate the sharing of experiences as well as enhancing their role as caregivers in cancer care. In response to the support needs identified, a support programme was developed, validated by a group of experts and implemented. There was an improvement in caregiver burden and caregivers and patient QoL post intervention. There an improvement change in the patients’ pain severity score post intervention. The worst pain and pain interference with daily activities also showed an improvements as well as the total symptom burden, the global distress index and psychosocial symptoms were improved post intervention. Conclusion: The study provided evidence that the support program had a positive influence on the QoL of the caregivers and decreased their caregiving burden. In addition, the patients also benefitted as their QoL, symptom burden and pain improved. The positive results support the conclusion that the programme was successful and emphasizes the importance of such programs to improve the lives of cancer patients and their caregivers. However, this was a pilot study without a control group and a small number of participants. Therefore, the results should be not overemphasized and considered cautiously.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2020